2006
DOI: 10.1086/498945
|View full text |Cite
|
Sign up to set email alerts
|

Is Evolution Necessary for Range Expansion? Manipulating Reproductive Timing of a Weedy Annual Transplanted beyond Its Range

Abstract: Ecologists often consider how environmental factors limit a species' geographic range. However, recent models suggest that geographic distribution also may be determined by a species' ability to adapt to novel environmental conditions. In this study, we empirically tested whether further evolution would be necessary for northern expansion of the weedy annual cocklebur (Xanthium strumarium) in its native North American range. We transplanted seedlings beyond the northern border and photoperiodically manipulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
96
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 59 publications
1
96
1
Order By: Relevance
“…replacement) at both sites in the beyond edge region, the 95% confidence intervals of seed production included values below one (not shown), indicating that even these populations, though best-adapted to this region, may not maintain themselves here based on data from this year of study. This is consistent with other studies that find adaptation of populations to conditions at the range edge, though absolute fitness below that necessary to sustain the populations when transplanted beyond the range edge [38], [39]. By contrast, other studies have not found a reduction in fitness beyond the range edge [40][42].…”
Section: Discussionsupporting
confidence: 92%
“…replacement) at both sites in the beyond edge region, the 95% confidence intervals of seed production included values below one (not shown), indicating that even these populations, though best-adapted to this region, may not maintain themselves here based on data from this year of study. This is consistent with other studies that find adaptation of populations to conditions at the range edge, though absolute fitness below that necessary to sustain the populations when transplanted beyond the range edge [38], [39]. By contrast, other studies have not found a reduction in fitness beyond the range edge [40][42].…”
Section: Discussionsupporting
confidence: 92%
“…(b) Implications for species distributions and range limits Genetic constraints on local adaptation have often been invoked to explain geographical range limits, but there are few empirical tests of this hypothesis (Bradshaw 1991;Davis & Shaw 2001;Blows & Hoffman 2005). Constraints on traits that determine the timing of reproduction may be particularly important in preventing range expansion to environments with shorter growing seasons typical of high latitudes and altitudes (Griffith & Watson 2006), and also in response to anthropogenic changes in climate and seasonality (Bradshaw & Holzapfel 2001;Franks et al 2007). Studies on a wide range of plant and animal species have compared levels of diversity at neutral maker loci between geographically central versus peripheral populations and many have found evidence of a decline in genetic variation towards range margins (reviewed in Eckert et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Etterson & Shaw 2001;Griffith & Watson 2006). A fitness trade-off between two traits occurs if natural selection cannot simultaneously improve both traits (Lande 1979;Lande & Arnold 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies of range limits using experiments (e.g., Geber and Eckhart 2005, Griffith and Watson 2006, Angert et al 2008, Kellermann et al 2009) and species distribution models (in the context of climate change [Thomas et al 2004, Lenoir et al 2008, Jiguet et al 2010) have mainly evaluated putative limiting abiotic factors (but see Samis and Eckert 2009). Empirical studies of range limits using experiments (e.g., Geber and Eckhart 2005, Griffith and Watson 2006, Angert et al 2008, Kellermann et al 2009) and species distribution models (in the context of climate change [Thomas et al 2004, Lenoir et al 2008, Jiguet et al 2010) have mainly evaluated putative limiting abiotic factors (but see Samis and Eckert 2009).…”
Section: Introductionmentioning
confidence: 99%